Population Pharmacokinetic/Pharmacodynamic Modeling of Glenzocimab (ACT017) a Glycoprotein VI Inhibitor of Collagen‐Induced Platelet Aggregation. (4th June 2020) - Renaud, Lionel; Lebozec, Kristell; Voors‐Pette, Christine; Dogterom, Peter; Billiald, Philippe; Jandrot Perrus, Martine; Pletan, Yannick; Machacek, Matthias
Abstract: Glenzocimab (ACT017) is a humanized monoclonal antigen‐binding fragment (Fab) directed against the human platelet glycoprotein VI, a key receptor for collagen and fibrin that plays a major role in thrombus growth and stability. Glenzocimab is being developed as an antiplatelet agent to treat the acute phase of ischemic stroke. During a phase I study in healthy volunteers, the population pharmacokinetics (PK) and pharmacodynamics (PD) of glenzocimab were modeled using Monolix software. The PK/PD model thus described glenzocimab plasma concentrations and its effects on ex vivo collagen‐induced platelet aggregation. Glenzocimab was found to have dose‐proportional, 2‐compartmental PK with a central distribution volume of 4.1 L, and first and second half‐lives of 0.84 and 9.6 hours. Interindividual variability in clearance in healthy volunteers was mainly explained by its dependence on body weight. The glenzocimab effect was described using an immediate effect model with a dose‐dependent half maximal inhibitory concentration: Larger doses resulted in a stronger effect at the same glenzocimab plasma concentration. The mechanism of the overproportional concentration effect at higher doses remained unexplained. PK/PD simulations predicted that 1000‐mg glenzocimab given as a 6‐hour infusion reduced platelet aggregation to 20% in 100% of subjects at 6 hours and in 60% of subjects at 12 hours after dosing. Simulations revealed a limited impact of creatinine clearance on exposure, suggesting that no dose adjustments were required with respect to renal function. Future studies in patients with ischemic stroke are now needed to establish the relationship between ex vivo platelet aggregation and the clinical effect.